Energy efficiency in industrial process heating systems - Gopalakrishnan, B. 1960- (Knovel, 2009)
Process heating systems are some of the largest energy-intensive systems in most industrial facilities and account for approximately 36% of industrial energy consumption. This article provides a summary of case studies resulting from an energy assessment of process heating systems at seven large industrial facilities.
Keywords: Industries -- Energy consumption.; Heating -- Energy consumption -- Evaluation.; Industrial engineering.; elektronické knihy; electronic books